Analisis Keamanan Informasi Pemerintah Kabupaten Minahasa Tenggara Menggunakan Indeks KAMI - Gala, Reynaldo A.P.P.; Sengkey, Rizal; Punusingon, Charles (Universitas Sam Ratulangi, 2020)
Abstract – Southeast Minahasa Regency is a regency that has maximized the benefits of Information and Communication Technology in supporting Southeast Minahasa programs towards a smart city. But unfortunately there is no information security framework that meets the SNI ISO/IEC 27001 standards. Therefore, it must be done in the field of security using the Information Security Management System (SMKI) method, namely the Information Security Index (KAMI). The level of information security maturity of the MITRA Regency Government is still very low or